Relationship between education level and women's participation in family planning programs (case study in Kampung KB, Ungaran Village, Kutowinangun Subdistrict, Kebumen Regency) - Anggun Pria Wibowo; Agung Nugroho; Erwando Erwando; Firdaus Firdaus; Ksatriawan Zaenuddin (Privietlab, 2025)
Uncontrolled population growth has consequences for the increase in birth rates in a region. One of the causes is low community participation, especially among women in family planning programs. This study aimed to analyze the relationship between education level and women's participation in family planning programs. The method used in this study was descriptive with a quantitative approach. The subjects of this study were all women in the fertile age couple category in Kampung KB, Ungaran Village, totaling 63. Research data were obtained through observation, questionnaire distribution, interviews, and documentation. Furthermore, the data were analyzed using descriptive analysis and the chi-square statistical test. The results of the analysis showed that there was no significant relationship between education level and women's participation in the family planning program (p = 0.069 > 0.05). These findings indicate that education is not a major determinant of women's decisions to participate in family planning programs. Most respondents with high levels of education were young PUS who had not yet planned to use contraceptives. Education continues to play an important role in increasing awareness and understanding of reproductive health, but its influence does not directly determine participation in family planning programs.